MyD88 signaling pathways: role in breast cancer - Zheng, Hongmei; Wu, Xinhong; Guo, Liantao; Liu, Jianhua (Frontiers in Oncology, 2024)
MyD88 plays a central role in breast cancer, exerting a multitude of effects that carry substantial implications. Elevated MyD88 expression is closely associated with aggressive tumor characteristics, suggesting its potential as a valuable prognostic marker and therapeutic target. MyD88 exerts influence over several critical aspects of breast cancer, including metastasis, recurrence, drug resistance, and the regulation of cancer stem cell properties. Furthermore, MyD88 modulates the release of inflammatory and chemotactic factors, thereby shaping the tumor's immune microenvironment. Its role in immune response modulation underscores its potential in influencing the dynamic interplay between tumors and the immune system. MyD88 primarily exerts intricate effects on tumor progression through pathways such as Phosphoinositide 3-kinases/Protein kinase B (PI3K/Akt), Toll-like Receptor/Nuclear Factor Kappa B (TLR/NF-κB), and others. Nevertheless, in-depth research is essential to unveil the precise mechanisms underlying the diverse roles of MyD88 in breast cancer. The translation of these findings into clinical applications holds great promise for advancing precision medicine approaches for breast cancer patients, ultimately enhancing prognosis and enabling the development of more effective therapeutic strategies.